2005
DOI: 10.1152/physrev.00024.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Channel Inactivation: Molecular Determinants and Modulation

Abstract: Voltage-gated sodium channels open (activate) when the membrane is depolarized and close on repolarization (deactivate) but also on continuing depolarization by a process termed inactivation, which leaves the channel refractory, i.e., unable to open again for a period of time. In the "classical" fast inactivation, this time is of the millisecond range, but it can last much longer (up to seconds) in a different slow type of inactivation. These two types of inactivation have different mechanisms located in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
226
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(236 citation statements)
references
References 490 publications
(424 reference statements)
9
226
0
1
Order By: Relevance
“…The gating modifications were consistent with modifications of the kinetics and destabilization of both the inactivated and, to a lesser extent, the activated state. L1649Q is localized in the S4 transmembrane segment of domain IV, a voltage sensor that is particularly important for activation-inactivation coupling (28), consistently with the large effects on inactivation that we have observed. A destabilization of fast inactivation is consistent with a dialysis-resistant I NaP component representing an intrinsic property of the mutant that does not require diffusible modulatory factors.…”
Section: Significancesupporting
confidence: 88%
“…The gating modifications were consistent with modifications of the kinetics and destabilization of both the inactivated and, to a lesser extent, the activated state. L1649Q is localized in the S4 transmembrane segment of domain IV, a voltage sensor that is particularly important for activation-inactivation coupling (28), consistently with the large effects on inactivation that we have observed. A destabilization of fast inactivation is consistent with a dialysis-resistant I NaP component representing an intrinsic property of the mutant that does not require diffusible modulatory factors.…”
Section: Significancesupporting
confidence: 88%
“…While values obtained for control fi bers corresponded to those reported ( Ulbricht, 2005 ), the i ' s of mdx 5cv fi bers were ‫ف‬ 1.5 times larger ( Fig. 3 B , bottom).…”
Section: Sodium Current Is Observed At Similar Levels In Control and supporting
confidence: 82%
“…Here, we found that between the fast and slow inactivation, bupivacaine preferably acted on the latter, for which the voltage-dependency and time constants were substantially changed. This finding is in agreement with the fact that the slow inactivation is thought to be accompanied by rearrangement of the channel pore in DIV [26] . use of the S(-)-enantiomer to reduce cardiac toxicity [11] .…”
Section: Discussionsupporting
confidence: 92%